(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
in order to achieve the development of directed qualities of strength, it is necessary to perform maximum muscle tension. That is why the main problem with strength training responsibility is to ensure a sufficiently high level of muscle tension in the process of performing exercises.